Bahasa Inggris - Ahmad Zaki Zein; Farahiyah Sartika (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
The Covid-19 pandemic led to a surge in online shopping and an increased use of Buy Now, Pay Later (BNPL) options like Shopee PayLater, particularly among university students who live away from home and have considerable financial needs. However, the impact of factors such as financial literacy, consumptive behavior, and lifestyle on the usage of these services, with financial behavior acting as a moderating factor, remains insufficiently understood. This research explores how financial literacy, consumptive behavior, and lifestyle influence the adoption of Shopee PayLater among university students in Malang City, with financial behavior as a moderating element. Using a quantitative approach, the study surveyed 100 students across five universities in Malang City and analyzed the data through Structural Equation Modeling (SEM) with SmartPLS 4.0. The results show that financial literacy and lifestyle do not significantly affect Shopee PayLater usage, whereas consumptive behavior exerts a positive influence. Additionally, financial behavior moderates the impact of both financial literacy and lifestyle on BNPL service usage and also influences the connection between consumptive behavior and Shopee PayLater utilization. These findings underscore the need for initiatives that not only enhance financial literacy but also focus on managing consumptive behavior and spending habits to mitigate students' dependency on BNPL services.